Cyphia deliae (Campanulaceae: Cyphioideae), a new species from South Africa and Eswatini - Steyn, Hester M.; van Wyk, Abraham E. (Phytotaxa, 2024)
Cyphia deliae, previously confused with C. bolusii, is described here as a new species. It is a range-restricted species known only from the Barberton Centre of Endemism, a biogeographical region that spans the border between South Africa and Eswatini. This species grows on rocky outcrops in montane grassland. Cyphia deliae can be differentiated from its morphologically most similar relative, C. bolusii, primarily by floral characters. A comparison of specific morphological features distinguishing Cyphia deliae from C. bolusii is provided. In accordance with IUCN Red List categories and criteria, a conservation assessment of Vulnerable B1ab(iii); C2a(i) is recommended for the new species.